Penerapan Media Pembelajaran Audio Visual Terhadap Peningkatan Hasil Belajar Peserta Didik Pada Mata Pelajaran PAI Kelas VII 6 Di SMP Negeri 7 Makassar - Ratika Nengsih; Ifut Novianti R.S; Ahmad Hakim (Education and Learning Journal, 2022)
The purpose of this study was to find out how the Application of Pendengaran Penglihatan Learning Alat Improve Student Learning Outcomes in PAI Subjects Class VII 6 at SMP Negeri 7 Makassar and to determine student learning outcomes using Pendengaran Penglihatan Learning Alat in PAI learning class VII 6 in SMP Negeri 7 Makassar. This research is a Classroom Action Research (CAR) which consists of two cycles, where each cycle consists of two meetings. The sample in this study was class VII 6 students at SMP Negeri 7 Makassar with a total of 28 students. The techniques used in collecting data in this study were observation, interviews, tests, and documentation. The test consists of two types, namely pre-test and post-test, the pre-test is carried out at the beginning of the meeting before the students are given treatment or the learning process by applying Audio Visual learning media while the post-test is carried out at the end of each meeting in each cycle. The data analysis technique used in this study is to use the formula for calculating the percentage and average value (Mean) for both student activity sheet data analysis and student learning outcomes. The results of this study are the application of Audio Visual learning media in PAI subjects is able to increase the sense of responsibility individually and in groups and the application of this Audio Visual learning model can improve student learning outcomes in PAI subjects. Thus the increase in student learning outcomes can be proven by the value of students who have increased and are getting better. The average value in the pre-test is 69.28 with a percentage of 42%, the average post-test value in the first cycle is 76.96 with a percentage of 71.42% and the post-test average value in the second cycle is 91, 42 with a percentage of 92.85%. The data proves that student learning outcomes can increase and have met the class success indicator, namely 80% with the application of Audio Visual learning media.